The influence of critical thinking skills on performance and progression in a pre-registration nursing program. (January 2015) - Pitt, Victoria; Powis, David; Levett-Jones, Tracy; Hunter, Sharyn
Summary Background The importance of developing critical thinking skills in preregistration nursing students is recognized worldwide. Yet, there has been limited exploration of how students' critical thinking skill scores on entry to pre-registration nursing education influence their academic and clinical performance and progression. Aim The aim of this study was to: i) describe entry and exit critical thinking scores of nursing students enrolled in a three year bachelor of nursing program in Australia in comparison to norm scores; ii) explore entry critical thinking scores in relation to demographic characteristics, students' performance and progression. Method This longitudinal correlational study used the Health Sciences Reasoning Test (HSRT) to measure critical thinking skills in a sample (n = 134) of students, at entry and exit (three years later). A one sample t-test was used to determine if differences existed between matched student critical thinking scores between entry and exit points. Academic performance, clinical performance and progression data were collected and correlations with entry critical thinking scores were examined. Results There was a significant relationship between critical thinking scores, academic performance and students' risk of failing, especially in the first semester of study. Critical thinking scores were predictive of program completion within three years. The increase in critical thinking scores from entry to exit was significant for the 28 students measured. In comparison to norm scores, entry level critical thinking scores were significantly lower, but exit scores were comparable. Critical thinking scores had no significant relationship to clinical performance. Conclusion Entry critical thinking scores significantly correlate to academic performance and predict students risk of course failure and ability to complete a nursing degree in three years. Students' critical thinking scores are an important determinant of their success and as such can inform curriculum development and selection strategies.